Callyspongiolide kills cells by inducing mitochondrial dysfunction via cellular iron depletion - Jaeyoung Ha (Nature Portfolio, 2021)
In order to elucidate how callyspongiolide, a potent cytotoxic marine natural product, kills human lung cancer cells, Ha and Park employed TS-FITGE technique, a label-free target identification method with thermal stability-shift-based fluorescence difference in 2-D gel electrophoresis, allowing them to observe protein-spot separation upon treatment in increasing temperatures. They found that callyspongiolide induces lysosomal dysfunction followed by mitochondrial dysfunction as well as iron depletion, which sheds light on the mechanism of action of callyspongiolide.